1975
DOI: 10.1021/es60105a004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of cinnabar by iron(III) in acid mine waters

Abstract: Fe(III) concentrations occurring in acid mine drainage water oxidized cinnabar (HgS), the most common natural mercury mineral. With Clpresent at environmental levels, significant mercury was released to solution. The rate of oxidation of cinnabar was much higher than the rate of mercury release to solution. Most of the mercury was bound to the remaining cinnabar by an unknown mechanism. An isotopic dilution technique was used to calculate the total mercury, both in solution and bound to the remaining cinnabar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…Experimental results have provided both direct and indirect evidences for the occurrence of Hg re-adsorption on cinnabar surface [7,10,13,15,24]. For instance, the amount of Hg released was found to be much lower than that of S (normally represented by SO 4 2− ), in strong disagreement with the stoichiometric estimation, indicating the adsorption of released Hg back on cinnabar particles [7,10,13,15]. Hg 2+ added into cinnabar suspension was observed to decrease quickly, further proving the occurrence of this process [10].…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Experimental results have provided both direct and indirect evidences for the occurrence of Hg re-adsorption on cinnabar surface [7,10,13,15,24]. For instance, the amount of Hg released was found to be much lower than that of S (normally represented by SO 4 2− ), in strong disagreement with the stoichiometric estimation, indicating the adsorption of released Hg back on cinnabar particles [7,10,13,15]. Hg 2+ added into cinnabar suspension was observed to decrease quickly, further proving the occurrence of this process [10].…”
Section: Introductionmentioning
confidence: 98%
“…However, previous studies showed that dissolution of mercury sulfide (e.g., cinnabar) can also serve as a continuous source of inorganic Hg in natural environment due to the fact that a variety of environmental factors can facilitate its dissolution. These factors include the presence of iron(III) in acidic water [4], sulfide in water [5], and dissolved organic matter (DOM) [6][7][8]. The enhanced dissolution of cinnabar could be an important process controlling Hg cycling in aquatic environments as this process would make the originally stable Hg more reactive and bioavailable, increasing the possibility of Hg transport, methylation and bioaccumulation, posing a great risk to humans and wildlife.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations